An information retrieval system for computerized patient records in the context of a daily hospital practice: the example of the Léon Bérard Cancer Center (France) - Biron, P.; Metzger, M.H.; Pezet, C.; Sebban, C.; Barthuet, E.; Durand, T. (Applied Clinical Informatics, 2014)
Background: A full-text search tool was introduced into the daily practice of Léon Bérard Center (France), a health care facility devoted to treatment of cancer. This tool was integrated into the hospital information system by the IT department having been granted full autonomy to improve the system.Objectives: To describe the development and various uses of a tool for full-text search of computerized patient records.Methods: The technology is based on Solr, an open-source search engine. It is a web-based application that processes HTTP requests and returns HTTP responses. A data processing pipeline that retrieves data from different repositories, normalizes, cleans and publishes it to Solr, was integrated in the information system of the Leon Bérard center. The IT department developed also user interfaces to allow users to access the search engine within the computerized medical record of the patient.Results: From January to May 2013, 500 queries were launched per month by an average of 140 different users. Several usages of the tool were described, as follows: medical management of patients, medical research, and improving the traceability of medical care in medical records. The sensitivity of the tool for detecting the medical records of patients diagnosed with both breast cancer and diabetes was 83.0%, and its positive predictive value was 48.7% (gold standard: manual screening by a clinical research assistant).Conclusion: The project demonstrates that the introduction of full-text-search tools allowed practitioners to use unstructured medical information for various purposes.Citation: Biron P; Metzger MH; Pezet C; Sebban C; Barthuet E; Durand T. An information retrieval system for computerized patient records in the context of a daily hospital practice: the example of the Léon Bérard Cancer Center (France)Appl Clin Inf 2014; 5: 191–205http://dx.doi.org/10.4338/ACI-2013-08-CR-0065
Keywords: Electronic health records; data mining; information storage and retrieval; user-computer interface